Axillary Ectopic Breast Tissue Primary Cancer: A Rare Presentation of a Common Disease: Axillary Ectopic Breast Cancer - Iacuzzo, Cristiana; Pellitteri, Cristina; Di Bella, Camillo; Abate, Anna; Giovanazzi, Riccardo (Archives of Breast Cancer, 2022)
Background: Carcinoma of ectopic breast tissue represents a rare condition. Ectopic glandular tissue is frequently located in the axilla, so ectopic breast lesions must be distinguished from other subcutaneous masses arising in this location. Case presentation: We describe the case of e 75 y/o woman presented to our department for the recent manifestation of an axillary cutaneous lesion. She underwent mammogram, breast ultrasound, fine-needle aspiration citology, breast MRI, thoraco-abdominal CT-scan and punch biopsy, and she was subsequently treated as a CUP-syndrome case. The final pathologic report showed the evidence of an ectopic breast tissue cancer. Conclusion: Despite the rarity of this condition, physicians should always keep in mind the possibility of ectopic BC in order to make an early diagnosis and adequately treat these patients.